2009
DOI: 10.1007/s12032-009-9232-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of the most common fusion genes in childhood acute lymphoblastic leukemia

Abstract: Contemporary protocols ensure high-remission rate and long-term free survival in children with acute lymphoblastic leukemia (ALL), but small percentage of patients is still incurable. Molecular genetic methods helped to establish submicroscopic classification as well as minimal residual disease follow-up, considered to be responsible for relapse. Our study enrolled 70 pediatric patients with de novo ALL, analyzed using reverse transcriptase-polymerase chain reaction for the presence of four major risk-stratify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 23 publications
1
9
0
1
Order By: Relevance
“…The five major riskstratifying translocations in patients with ALL are BCR-ABL, ETV6-RUNX1, MLL-AF4, SIL-TAL1 and TCF3-PBX1 (Lazic et al, 2010;Iacobucci et al, 2012). The frequency of some of the FO in this study is comparable to the previous studies from Pakistan and other parts of the world (Gaynon et al, 1997;Iacobucci et al, 2012).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The five major riskstratifying translocations in patients with ALL are BCR-ABL, ETV6-RUNX1, MLL-AF4, SIL-TAL1 and TCF3-PBX1 (Lazic et al, 2010;Iacobucci et al, 2012). The frequency of some of the FO in this study is comparable to the previous studies from Pakistan and other parts of the world (Gaynon et al, 1997;Iacobucci et al, 2012).…”
Section: Discussionsupporting
confidence: 80%
“…Most notable was the high frequency of the BCR-ABL that was 44.5% as compared to population study in Europe where it is not so high (Van Dongen et al, 1999;Lazic et al, 2010;Iacobucci et al, 2012) except in Sudan, Africa (Siddique et al, 2010) while BCR-ABL has been reported to be totally absent in Saudi Arabian pediatric ALL patients (El-sissy et al, 2006;Siraj et al, 2006). The Philadelphia chromosome is present in children with ALL and leads to the production of BCR-ABL fusion protein with tyrosine kinase activity.…”
Section: Discussionmentioning
confidence: 97%
“…The incidence of TEL-AML1 fusion in 334 Italian and German children with ALL was 18.9% (Borkhardt et al, 1997) and 22-27% in German children alone (Papadhimitriou et al, 2008), as compared to 22.5% in 617 children from UK (Harrison, 2000). Similarly the prevalence of TEL-AML1 transcript in acute lymphoblastic leukemia patients in Serbia is 17.1% (Lazic et al, 2010) and 20% in Brazil (Magalhaes et al, 2000). Frequency of TEL-AML1 in Greek pediatric patients seems comparable to that in other European countries, found as 24.3% in 120 ALL children (Papadhimitriouet al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, genetic profiles nowadays have diagnostic, prognostic and therapeutic applications in several fields, especially cancer care. One of the most prominent examples for the role of genetic profiling in oncology is the detection of fusion genes and rearrangements in pediatric leukemia (30).…”
Section: Molecular Genetic Markers In Diagnosis Prognosis and Followmentioning
confidence: 99%